2021
DOI: 10.4269/ajtmh.20-1563
|View full text |Cite
|
Sign up to set email alerts
|

The Hajj and COVID-19: How the Pandemic Shaped the World’s Largest Religious Gathering

Abstract: The Hajj pilgrimage, one of the five pillars of Islam, is held in Saudi Arabia in the second week of Dhu’l-Hijjah, the last month of the Islamic calendar. It is one of the world’s largest mass gatherings, constituting more than 2.5 million Muslim pilgrims from more than 180 countries. The COVID-19 pandemic posed a significant public health threat for such mass gatherings. Thus, a health risk assessment for the 2020 Hajj was held by the Saudi Arabia Ministry of Health and the WHO Collaborating Centre for Mass G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 9 publications
0
49
0
Order By: Relevance
“…Not only this but also internal standard operating procedures and health precautions that ought to be taken in managing Hajj needs to be crystalised and informed to all stakeholders to ensure that Hajj price is not affected due to the changes brought. These changes are evident from the way year 2020 Hajj and Umrah is managed in the midst of the pandemic by Saudi Arabia where it is stated that that is described by Hashim et al (2021) as follows:…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only this but also internal standard operating procedures and health precautions that ought to be taken in managing Hajj needs to be crystalised and informed to all stakeholders to ensure that Hajj price is not affected due to the changes brought. These changes are evident from the way year 2020 Hajj and Umrah is managed in the midst of the pandemic by Saudi Arabia where it is stated that that is described by Hashim et al (2021) as follows:…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…It is also stated that a total of 1,000 pilgrims from 160 different nationalities and all residents of Saudi Arabia performed the Hajj in 2020 where there were no confirmed COVID-19 cases among the pilgrims during or after the pilgrimage (Hashim et al , 2021). This has been considered and highlighted as a successful case study that proves the effectiveness of the risk mitigation mechanisms adopted by Saudi Arabia (Jokhdar et al , 2020).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…For example, Carlin et al ( 2021 ) evaluated the impact of the COVID-19 pandemic on mass gatherings for hockey and basketball games in North America, Hughes et al ( 2020 ) conducted a study on the framework of sports in Australia, Mat et al ( 2020 ) evaluated and found COVID-19 contamination in Malaysia because of mass gatherings, Nyasulu et al ( 2021 ) argued that the COVID-19 outbreak emerged in Malawi-Southeastern Africa as a result of sociopolitical mass gatherings, Teixeira ( 2020 ) highlighted a possible transmission of COVID-19 due to mass gatherings in Brazil, Yezli and Khan ( 2020 ) highlighted possible health risks from the transmission of COVID-19 due to mass gatherings in Jeddah-KSA. A lot of research has also been conducted on religious mass gatherings and religious tourism with the perspective of COVID-19, including but not limited to the studies of Ahmed and Memish ( 2020 ), Atique and Itumalla ( 2020 ), Ebrahim and Memish ( 2020 ), Hoang et al ( 2020 ), Mat et al ( 2020 ), Mubarak ( 2020 ), Mubarak and Zin ( 2020 ), Quadri ( 2020 ), Rodriguez-Morales et al ( 2020 ), VanderWeele ( 2020 ), Yezli and Khan ( 2020 ), Hashim et al ( 2021 ), Hsu et al ( 2021 ), Sokhna et al ( 2021 ), and Yezli and Khan ( 2021 ). Although some of these studies address the issue partially or indirectly, there is still a clear gap in the literature regarding real determinants of the implementation of SOPs for COVID-19 in mass gatherings.…”
Section: Introductionmentioning
confidence: 99%
“…polio and meningitis), education campaigns, and country-specific restrictions, such as the restrictions applied to the countries impacted by the Ebola crisis 4 . Given that a large number of pilgrims take part in Hajj from more than 180 countries 5,6 , it can potentially serve as a superspreading event, and an outbreak can have significant global impacts.…”
Section: Introductionmentioning
confidence: 99%